1997
DOI: 10.5465/amr.1997.9707180265
|View full text |Cite
|
Sign up to set email alerts
|

When Employees Feel Betrayed: A Model of How Psychological Contract Violation Develops

Abstract: The psychological contract held by an employee consists of beliefs about the reciprocal obligations between that employee and his or her organization. Violation refers to the feelings of anger and betrayal that are often experienced when an employee believes that the organization has failed to fulfill one or more of those obligations. This article provides a model outlining the psychological sensemaking processes preceding an employee's experience of psychological contract violation. It also identifies factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

64
2,088
8
63

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,880 publications
(2,288 citation statements)
references
References 42 publications
(69 reference statements)
64
2,088
8
63
Order By: Relevance
“…Consistent with this assertion, prior studies (Elangovan et al, 2007;Elangovan & Shapiro, 1998;Harmon et al, 2015;Morrison & Robinson, 1997) found that erosion of trust is stronger, when the trustor perceives that the undesirable episode stemmed from a trustee's conscious decision of refusing to meet trustor's expectations. When the trustor feels that the counterpart at least tries to do the right thing, but could not meet trustor's expectations, some credit can still be given to the offender and the fault may be seen as temporary and less likely to be repeated in the future.…”
Section: Hypothesissupporting
confidence: 65%
“…Consistent with this assertion, prior studies (Elangovan et al, 2007;Elangovan & Shapiro, 1998;Harmon et al, 2015;Morrison & Robinson, 1997) found that erosion of trust is stronger, when the trustor perceives that the undesirable episode stemmed from a trustee's conscious decision of refusing to meet trustor's expectations. When the trustor feels that the counterpart at least tries to do the right thing, but could not meet trustor's expectations, some credit can still be given to the offender and the fault may be seen as temporary and less likely to be repeated in the future.…”
Section: Hypothesissupporting
confidence: 65%
“…A number of research studies (e.g. Huang and Hsiao, 2007;Mathieu and Zajac, 1990;Morrison and Robinson, 1997;Rayton, 2006;Yousef, 2002) have shown that job satisfaction provided a positive direct influence on organizational commitment. However, the survey results in this study have shown that job satisfaction has a mediating influence on the relationship between work group identification and the two forms of organization commitment.…”
Section: Discussion Of Research Findingsmentioning
confidence: 99%
“…Many studies in various contexts have shown a positive relationship between job satisfaction and commitment (Huang and Hsiao, 2007;Martin and Roodt, 2008;Mathieu and Zajac, 1990;Meyer et al 2002;Morrison and Robinson, 1997;Rayton, 2006;Yousef, 2002). In addition, some researchers found that job satisfaction is important in understanding the influence of a number of variables on organisational commitment.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…The violation of a psychological contract is an emotional experience of disappointment, frustration, anger and resentment that might emanate from the way the employee interprets and feels about the psychological contract breaches and their circumstances (Morrison & Robinson, 1997).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The psychological contract is the set of beliefs about the reciprocal obligations between an individual and an organization (Morrison & Robinson, 1997). Even before joining an organization, a psychological contract begins to form, through pre-existing expectations about the organization.…”
Section: Theoretical Frameworkmentioning
confidence: 99%